Cultural Democracy in Learning English at Madura Boarding School - Moh. Hafidz; Moh. Arief Wahyudi (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
English is the language of daily life trains communication skills and job needs. This researchdescribes and analyzes about how cultural democracy in learning English is applied, maintaininglocal language (Madurese language) and the role of kiai in curriculum making? The benefits of thisstudy as a theoretical reference and practice in learning English to maintain local language andculture. This research was conducted at Madura Islamic boarding school using descriptivequalitative approach with ethnographic research design, data collection techniques throughobservation, interviews and documentation. While the way to analyzeis familiarizing and organizing,coding and reducing, and interpreting and representing. The results are always encouraging tutorsand students to shape the environment of English and develop students' knowledge with vocabularymastery through the “settoran” method. Conduct observations and teachings through “FantsyMorning” and “Bazar Exhibition” and involve managers and alumni in making policies. Learninguses cooperative models by writing text in groups and reading text aloud. Speaking using Englishas a pesantren regulation. Maintaining pesantren culture, starting to dress and learning activities.Conducting curriculum development through deliberation to evaluate the entire set of activities andlearning outcomes. Assessing vocabulary mastery, writing skill and speaking skill successively.Learning a cultural democracy-based language maintains the pesantren's value system andenhances new abilities and knowledge of English and supports Madura (enggi-bhunten). While therole of the kiai in making curriculum is that there are those who are involved directly and indirectly.